Development of poly(lactic acid)/kenaf-derived cellulose with thermally grafted aminosilane and epoxidized plant oils for potential food packaging applications - Tee, Yee Bond (2015)
Poly(lactic acid) (PLA) biocomposites aimed for food packaging applications were developed from the present research. Seventeen PLA blends were studied and one optimum ternary biocomposite was finalized to conclude the work. Kenaf-derived cellulose (C), 3-aminopropyltriethoxysilane (APS), epoxidized soybean oil (ESO), and epoxidized palm oil (EPO) were the core materials tested for reinforcement. It is typical that natural fibers-filled plastic composites to report poor interfacial adhesion due to their distinct difference in polarity. To improve the interfacial adhesion, kenaf-derived cellulose was treated with silane coupling agent, APS prior to filling into PLA. Moreover, they were subjected to thermal treatment for permanent cross-linking upon acknowledging that desorption of chemicals is highly undesirable in food-related packaging. Also distinct to typical practices, C was thermally grafted with various silane concentrations (5, 8, and 11 wt%) and these silane-grafted cellulose (SGC) were termed as SGC5, SGC8, and SGC11. From investigation via Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), morphology analysis, size distribution, and density measurement, it was conclusive that (i) cellulose was derived from kenaf, and (ii) silane was effectively grafted onto the cellulose. 30 wt% of C, SGC5, SGC8, and SGC11 were respectively meltcompounded into PLA and hot-pressed into 0.3-mm sheets with the aim to develope biocomposite with optimum properties. With highest reinforcement in tensile strength, water resistance, dimensional stability, crystallinity, and oxygen barrier, PLA/SGC8 was concluded as the biocomposite for development towards packaging applications. Nonetheless, all biocomposites did not improve PLA’s brittle nature. Concurrently, they reduced the toughness. With sustainability in mind, EPO and commercialized ESO were plasticizers considered to reinforce these properties. Out of the analyses subjected, it is noteworthy that EPO can transition PLA to become ductile and tougher at lower concentration than ESO which denoted its competency as alternative bioplasticizer. Comprehending EPO’s potential as reactive plasticizer, the research continued with EPO addition at various loadings (3, 5, and 10 wt%) into PLA/SGC8 composite. Peak shifts were observed in the FTIR spectra of PLA/SGC8/EPO blends which was absent in PLA/C/EPO. It was proposed that EPO could reactively interact with PLA and SGC which therefore functioned as a compatible layer between the interfaces. The proposed mechanism was validated from morphology analysis plus improvement in water resistance, mechanical, and thermal properties of PLA/SGC8/EPO blends. Of all ternary blends, PLA/SGC8/EPO5 reported optimum reinforcement in EAB and toughness. The oxygen and water vapour barrier of this optimized blend suggested potential as packaging material for salad mixes. Conceding that the developed biocomposite can be impractical if it cannot be fabricated into functional product, PLA/SGC8/EPO5 together with PLA/EPO10, PLA/C/EPO5, and PLA (as reference) sheets were selectively subjected to thermoformability and overall migration test. While PLA/C/EPO5 failed both tests, PLA/SGC8/EPO5 was thermoformable and constituent migration was within the stipulated overall migration limit. These practical tests reasserted the competency of the presently developed biocomposite to be fabricated towards food packaging applications.